A Combined Kinetic and Thermodynamic Approach for the Interpretation of Continuous‐Flow Heterogeneous Catalytic Processes. Issue 24 (15th April 2013) - Bortolini, Olga; Cavazzini, Alberto; Giovannini, Pier Paolo; Greco, Roberto; Marchetti, Nicola; Massi, Alessandro; Pasti, Luisa
Abstract The heterogeneous proline‐catalyzed aldol reaction was investigated under continuous‐flow conditions by means of a packed‐bed microreactor. Reaction‐progress kinetic analysis (RPKA) was used in combination with nonlinear chromatography for the interpretation, under synthetically relevant conditions, of important mechanistic aspects of the heterogeneous catalytic process at a molecular level. The information gathered by RPKA and nonlinear chromatography proved to be highly complementary and allowed for the assessment of optimal operating variables. In particular, the determination of the rate‐determining step was pivotal for optimizing the feed composition. On the other hand, the competitive product inhibition was responsible for the unexpected decrease in the reaction yield following an apparently obvious variation in the feed composition. The study was facilitated by a suitable 2D instrumental arrangement for simultaneous flow reaction and online flow‐injection analysis.